What helps adolescents with obesity to enjoy and participate in physical activity? - Constanze Greule; Gorden Sudeck; Katrin Ziser; Rebecca Erschens; Peter Martus; Katrin Elisabeth Giel; Isabelle Mack; Alisa Weiland; Guido Zurstiege; Stephan Zipfel; Stefan Ehehalt; Florian Junne; et al. (German Journal of Exercise and Sport Research, 2026)
Purpose The main purpose was to identify clusters of adolescents with overweight or obesity characterized by the satisfaction of basic psychological needs, exercise-related barriers, and social support by family members and friends. This served the overarching goal of informing hypotheses for tailored research approaches in physical activity promotion considering a stronger focus on physical activity enjoyment. Methods Cross-sectional baseline data from 125 adolescents with overweight or obesity aged 12–17 years participating in the STARKIDS study were analyzed. A hierarchical cluster analysis was carried out, and the resulting number of clusters was optimized using the K‑means method. Subsequently, differences between individual cluster membership regarding physical activity enjoyment and physical activity levels were analyzed to further describe the identified subgroups. Results Four psychosocial clusters were identified as (1) overall supportive, (2) overall hindering, (3) individually supportive, and (4) socially supportive. The clusters differ significantly in terms of physical activity enjoyment ( p η 2 = 0.370) and physical activity behavior ( p η 2 = 0.145), with the highest values of enjoyment in clusters (1) and (3). Conclusion The present results indicate promising opportunities for future research on promoting physical activity enjoyment considering adolescents’ individual and social resources.